VMock : pivoting to succeed and scale in a technology startup company - Sawhney, Mohanbir, (SAGE Knowledge. Cases., 2017)
In 2010, Salil Pande founded VMock, an online product that helped MBA students prepare for job interviews. Students could upload their video interviews and get feedback from mentors and peers. Four years later, VMock pivoted from an interview feedback product to a "Smart Resume" product that focused on improving resumes. The pivot was based on the insight that job candidates first needed help fixing their resumes before they could obtain and prepare for interviews. Further, the interview feedback product was difficult to scale as it relied on human feedback. The Smart Resume product, on the other hand, was powered by machine learning and artificial intelligence technology, making it more scalable and allowing VMock to evolve its offering from a product to a platform for managing careers. VMock had forged strong relationships with top business schools in the United States and Europe and its Smart Resume platform had been well received by the market.